Chimeric papillomavirus-like particles expressing a foreign epitope on capsid surface loops - Slupetzky, Katharina (2001)
Neutralization capsid epitopes are important determinants for antibody-mediated immune protection against papillomavirus (PV) infection and induced disease. Chimeric L1 major capsid proteins of the human PV type 16 (HPV-16) and the bovine PV type 1 (BPV-1) with a foreign peptide incorporated into several capsid surface loops self-assembled into pentamers or virus-like particles (VLP). Binding patterns of neutralizing monoclonal antibodies (MAb) and immunization of mice confirmed (i) that regions around aa 282–286 and 351–355 contribute to neutralization epitopes and identified the latter region as an immunodominant site and (ii) that placing a foreign peptide in the context of an assembled structure markedly enhanced its immunogenicity. Pentamers disassembled from wild-type HPV-16 and BPV-1 VLPs displayed some of the neutralization epitopes that were detected on fully assembled VLPs, but were deficient for binding a subset of neutralizing MAb that inhibit cell attachment.